The underground economic activity and the desire for corruption in the border region (study of Bengkayang District, West Kalimantan) - Aloysius Hari Kristianto; Jones Parlindungan Nadapdap; Pramatatya Resindra Widya (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
Underground economic activity is a situation that needs particular and ongoing attention. This tendency is detrimental to municipal income and is associated with corrupt behaviors and taxation. The purpose of this investigation is to identify and assess the practices of the underground economy, as well as the potential for corrupt conduct and tax evasion. The analytical tool was perhaps a qualitative method with a chosen strategy to identify knowledge sources (respondents) with subjects such as liquor producers, coffee shops, and street food vendors in the Bengkayang border area. The data collection method was carried out using a triangulation approach, namely an in-depth interview, observation, and recording/documentation. The data analysis approach was conducted using data reduction, data presentation, and verification. This study suggests that the presence of corrupt activity in collecting bribes and offering bribes is carried out in cash without going through an automated money processing mechanism such as giving false receipts. Increasing the level of corruption in society will contribute to an increase in the velocity of money. The need for massive surveillance of individuals and the introduction of Penta helix elements to shape synergies between actors and to start integrating and developing electronic/digital structures in any financial activity using the e-government system.